Intraoperative Seizures: Anesthetic and Antiepileptic Drugs - Uribe, Alberto; Zuleta-Alarcon, Alix; Kassem, Mahmoud; Sandhu, Gurneet S.; Bergese, Sergio D. (Current Pharmaceutical Design, 2017)
Background: Epilepsy is a common condition with up to 1% prevalence in the general population. In the perioperative course of neurologic surgery patients, the use of prophylactic and therapeutic antiepileptic drugs is a common practice. Nonetheless, there is limited evidence supporting the use of prophylactic antiepileptics to prevent perioperative seizures and there are no guidelines for which anesthetic technique is preferred. Objective: To discuss the seizurogenic potential of anesthetic drugs and to discuss intraoperative seizures in neurosurgical patients. Method: We performed a search of the literature available in PubMed and Ovid MEDLINE. We also included articles identified in the review of the references of these articles. Results: The incidence of seizures is heterogenic among neurosurgical patients. Seizure prophylaxis is widely administered despite limited available evidence of its effectiveness. In epileptic patients, the recommendation is to continue antiepileptic drugs in the perioperative setting. In these patients, anesthesiologists may also limit the use of medications that alter the seizure threshold and avoid medications that pose significant pharmacological interaction with antiepileptic drugs. Conclusion: In conclusion, a knowledgeable multidisciplinary perioperative team is essential to avoid, identify and treat intraoperative seizures competently. In patients with a history of epilepsy it is recommended to continue antiepileptic therapy. Therefore, clinical judgment should guide the decision of administering seizure prophylaxis in neurosurgery patients according to an individual assessment of potential risk for seizures. Furthermore, there is a need for randomized controlled trials that support new protocols and/or guidelines for anesthetic and perioperative regimens to prevent and treat intraoperative seizures.
Keywords: anesthetics